Coccoloba uvifera (L.) (Polygonaceae) Fruit: Phytochemical Screening and Potential Antioxidant Activity - Maira Rubi Segura Campos; Jorge Ruiz Ruiz; Luis Chel-Guerrero; David Betancur Ancona (Journal of Chemistry)
The flora of Latin America attracts gaining interest as it provides a plethora of still unexplored or underutilized fruits that can contribute to human well-being due to their nutritional value and their content of bioactive compounds. Antioxidant compounds are now of considerable interest due to their effect of preventing or delaying aging and their apparent involvement in prevention of numerous human diseases, including cancer, atherosclerosis, Alzheimer’s disease, inflammation, and rheumatoid arthritis. In this work, the fruit of Coccoloba uvifera (L.) was investigated for their in vitro antioxidant capacity using two assays based on reactions with a relatively stable single reagent radical (Trolox equivalent antioxidant capacity, TEAC; and DPPH free radical scavenging assay, DPPH), two assays based on chelating of metallic cations, and one based on the reduction of oxidized species. The TEAC value on ABTS radical, DPPH scavenging activity, ion chelation, and reducing power were found to be 897.6 μM of Trolox/100 g of sample, 22.8% of DPPH free radical scavenging, 11.3% of Cu2+-chelating activity, 23.9% of Fe2+-chelating activity, and a Fe2+-reducing power of 0.76 mg/mL, respectively. The free radical scavenging and antioxidant characteristics of C. uvifera may be due to the presence of diverse phytochemicals in the fruit as anthocyanins, ascorbic acid, phenolic compounds, and flavonoids.